Discordant nature of Cd in PbSe: off-centering and core-shell nanoscale CdSe precipitates lead to high thermoelectric performance - Cai, Songting; Hao, Shiqiang; Luo, Zhong-Zhen; Li, Xiang; Hadar, Ido; Bailey, Trevor P; Hu, Xiaobing; Uher, Ctirad; Hu, Yan-Yan; Wolverton, Christopher; Dravid, Vinayak P; Kanatzidis, Mercouri G (Energy & environmental science, 2020)
We report a novel hierarchical microstructure in the PbSe-CdSe system, which collectively contributes to significant enhancement in thermoelectric performance, with ZT ave ∼ 0.83 across the 400-923 K temperature range, the highest reported for p-type, Te-free PbSe systems. We have investigated the local atomic structure as well as the microstructure of a series of PbSe- x CdSe materials, up to x = 10%. We find that the behavior of the Cd atoms in the octahedral rock salt sites is discordant and results in off-center displacement and distortion. Such off-centered Cd in the PbSe matrix creates (1) L-Σ electronic energy band convergence, (2) a flattened L band, both contributing to higher Seebeck coefficients, and (3) enhanced phonon scattering, which leads to lower thermal conductivity. These conclusions are supported by photoemission yield spectroscopy in air (PYSA), solid state 111 Cd, 77 Se NMR spectroscopy and DFT calculations. Above the solubility limit (>6%CdSe), we also observe endotaxial CdSe nano-precipitates with core-shell architecture formed in PbSe, whose size, distribution and structure gradually change with the Cd content. The nano-precipitates exhibit a zinc blende crystal structure and a tetrahedral shape with significant local strain, but are covered with a thin wurtzite layer along the precipitate/matrix interface, creating a core-shell structure embedded in PbSe. This newly discovered architecture causes a further reduction in lattice thermal conductivity. Moreover, potassium is found to be an effective p-type dopant in the PbSe-CdSe system, leading to an enhanced power factor, a maximum ZT of ∼1.4 at 923 K for Pb 0.98 K 0.02 Se-6%CdSe. Off-centering and core-shell nanoscale CdSe precipitates lead to high thermoelectric performance for p-type, Te-free PbSe systems.